Clinical features and outcomes in patients with non-acoustic cerebellopontine angle tumours. Issue 6 (1st June 1999) - Mallucci, Connor L; Ward, Victoria; Carney, A Simon; O'Donoghue, Gerard M; Robertson, Iain
Abstract : OBJECTIVES: Non-acoustic tumours of the cerebellopontine angle differ from vestibular schwannomas in their prevalence, clinical features, operative management, and surgical outcome. These features were studied in patients presenting to the regional neuro-otological unit. METHODS: A retrospective analysis of clinical notes identified 42 patients with non-acoustic tumours of the cerebellopontine angle. Data were extracted regarding presenting clinical features, histopathological data after surgical resection, surgical morbidity and mortality, and clinical outcome (mean 32 months follow up). RESULTS: The study group comprised 25 meningiomas (60%), 12 epidermoid cysts/cholesteatomata (28%), and five other tumours. In patients with meningiomas, symptoms differed considerably from patients presenting with vestibular schwannomas. Cerebellar signs were present in 52% and hearing loss in only 68%. Twenty per cent of patients had hydrocephalus at the time of diagnosis. After surgical resection, normal facial nerve function was preserved in 75% of cases. In the epidermoid group, fifth, seventh, and eighth nerve deficits were present in 42%, 33%, and 66% respectively. There were no new postoperative facial palsies. There were two recurrences (17%) requiring reoperation. Overall, there were two perioperative deaths from pneumonia and meningitis. CONCLUSIONS: Patients with non-acoustic lesions of the cerebellopontine angle often present with different symptoms and signs from those found in patients with schwannomas. Hearing loss is less prevalent and cerebellar signs and facial paresis are more common as presenting features. Hydrocephalus is often present in patients presenting with cerebellopontine angle meningiomas. Non-acoustic tumours can usually be resected with facial nerve preservation.